Pengaruh Penggunaan Panduan Tanggap Bencana Terhadap Strategi Koping Keluarga Dalam Menghadapi Kerentanan Bencana Tsunami Di Desa Gunturharjo Kabupaten Wonogiri - Suyanto Suyanto; Hartono Hartono (Poltekkes Kemenkes Surakarta, 2019)
Background: Tsunamis are one of the most frequent disasters in Indonesia and are very risky along the southern coast of the island of Java, including the area of Wonogiri Regency which has a southern coastline. The tsunami resulted in losses not only of loss of property and lives but also of the psychosocial impact of mental health disorders. Therefore tsunami disaster preparedness is carried out not only on physical aspects but also on psychosocial aspects such as disaster response by improving family coping strategies. Methods: This study wanted to see the effect of using disaster response guidebooks on family coping strategies to deal with tsunamis. The population of this study was people living in the coastal area of Nampu, Guntur Harjo sub-district, Parang Gupito, Wonogiri Regency, Central Java, with a sample of 240 households. The study design used one group pre-post test with a quasi-experimental approach where the research data collected were analyzed using a Chi-Square test. Result: The results showed that p-Value = 0,000 <0,005 so it can be concluded that there are differences in family coping strategies between before and after using the tsunami disaster response guidelines. Conclusion: It is recommended to continue preparedness efforts and disaster response efforts using existing guidelines and conduct research on areas that have different characteristics.